The safety of co-administration of Bacille Calmette-Guérin (BCG) and influenza vaccines. - Paola Villanueva; Ushma Wadia; Nigel W Crawford; Nicole L Messina; Tobias R Kollmann; Michaela Lucas; Laurens Manning; Peter Richmond; Laure F Pittet; Nigel Curtis (PLoS ONE)
Background With the emergence of novel vaccines and new applications for older vaccines, co-administration is increasingly likely. The immunomodulatory effects of BCG could theoretically alter the reactogenicity of co-administered vaccines. Using active surveillance in a randomised controlled trial, we aimed to determine whether co-administration of BCG vaccination changes the safety profile of influenza vaccination. Methods Participants who received influenza vaccine alone (Influenza group) were compared with those who also received BCG-Denmark vaccine in the contralateral arm (Influenza+BCG group). Data on the influenza vaccination site were collected using serial questionnaires and active follow-up for 3 months post vaccination. Results Of 1351 participants in the Influenza+BCG group and 1418 participants in the Influenza group, 2615 (94%) provided influenza vaccine safety data. There was no significant difference in the proportion of participants with any local adverse reaction between the Influenza+BCG group and the Influenza group (918/1293 [71.0%] versus (906/1322 [68.5%], p = 0.17). The proportion of participants reporting any pain, erythema and tenderness at the influenza vaccination site were similar in both groups. Swelling was less frequent (81/1293 [6.3%] versus 119/1322 (9.0%), p = 0.01) and the maximal diameter of erythema was smaller (mean 1.8 cm [SD 2.0] versus 3.0 cm [SD 2.5], p<0.001) in the Influenza+BCG group. Sixteen participants reported serious adverse events: 9 participants in the Influenza+BCG group and 7 in the Influenza group. Conclusions Adverse events following influenza vaccination are not increased when BCG is co-administered.